An Arzela-Ascoli type theorem for random functions - Joseph P. Noonan; Henry M. Polchlopek (International Journal of Mathematics and Mathematical Sciences)
A Theorem involving the convergence of random functions is presented. The Theorem is based upon the Arzela-Ascoli Theorem of Real Analysis. The development here may be useful in transient or asymptotic analysis of random functions and linear systems theory.